(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background Italy is Europe’s third largest pharmaceutical market, yet it ranks only ninth in the number of NIH-registered clinical trials per capita. The aim of our study was to explore stakeholders’ perception of Italy as place to undertake clinical trials, and to estimate the potential economic impact of selected reforms in terms of incremental trial activity. Methods The Survey of Attitudes towards Trials in Europe (SAT-EU Study) was an anonymous, web-based survey which systematically assessed factors impacting clinical trial site selection in Europe. Estimates of Italian economic impact were developed in collaboration with AICRO (Association of Italian Contract Research Organisations). Results Responses were obtained from 485 professionals in 34 countries (15% residing in Italy) representing over 100 institutions, spanning BioPharma Clinical Research Organizations (CROs), and Academic Clinical Trial Units (CTUs). Italy ranked tenth of twelve in terms of accessibility and transparency of information required to run clinical trials, and last with respect to predictability and speed of Ethics Committees. Costs of running clinical trials were not considered critical, whereas, fragmented and slow approval process was. Streamlined centralized trial authorization would translate into an estimated 1.1 billion Euros of incremental trial investments over three years. Conclusions Clinical trial professionals consider Italy’s governance of clinical research suboptimal, among the worst in Europe, and indicate that much could be done to make Italy more attractive for clinical trial investments. The present study also provides evidence about stakeholders’ willingness to invest in trials and its economic consequences provided effective reforms are put in place.